The strategic roles of culture to foreign corporations in Malaysia / Khairul Azfar Adzahar, Mohd Fazil Jamaludin and Mohd Shafiz Saharan - Adzahar, Khairul Azfar; Jamaludin, Mohd Fazil; Saharan, Mohd Shafiz (Universiti Teknologi MARA, Kedah, 2022)
Even though Malaysia is made up of many ethnic groups, the country has made significant headway in the influx of foreign brands and companies operating locally. However, little is known about the characteristics that contribute to success, making it difficult for Malaysia to continue capitalising on upcoming prospects and for multinational firms to properly direct their business activities in Malaysia. Due to the lack of organising frameworks for global strategy, firms must comprehend the strategic relevance of culture in order to thrive in the dynamic Malaysian business climate and to avoid making potential mistakes when conducting business in the country. Diversity in the workplace is inevitable in modern business, as organisations become increasingly diverse in terms of not only gender and age, but also race and ethnicity. Consequently, the study of workplace culture is imperative for establishing a cohesive human resources sphere in a heterogeneous workplace setting. Several established cultural frameworks, such as Geert Hofstede’s five dimensions of culture, have been identified to elicit the required information. Such dimensions include power distance, uncertainty avoidance, individualism versus collectivism, masculinity versus femininity, and time orientation. In addition, Fons Trompenaars’s seven cultural frameworks are frequently employed in the study of intercultural management and business in order to gain a comprehensive knowledge of society’s cultural frame of reference. The EPG model developed by Perlmutter is used to gauge a firm’s management orientation in its respective global market. Financial, economic, and legal liberation offer investors more access to the vast and diversified global market. As a consequence, recognising and embracing the notion of diversity in the workplace is becoming more crucial, as it might alter the work environment and intensify the strategic goals and objectives of the organisation (Patrick & Kumar, 2012). Differences amongst groups and individuals inside an organisation can be obvious, such as gender, race, and ethnicity, as well as invisible, where they can be characterised by employees’ values, beliefs, and actions that differ according to race, ethnicity, age, lifestyles, physical abilities, and gender (Foma, 2014). Choosing the proper orientation is arguably one of the most critical aspects in a firm’s ability to successfully adapt to a culturally diverse marketplace. Individuals and firms may hold conflicting viewpoints on how matters are conducted and how they should be implemented. An indicator of a company’s management orientation would be the adoption of nationality-based hiring practises for managerial positions. Firms with an ethnocentric orientation believe that their way of handling matters is the best way to operate and that there is no need to adapt to the local cultural practices because they are perceived to be of little or no value to the organisation, which is a clear bias that domestic approaches to business are vastly superior (Onodugo et al., 2017). In contrast, a firm that adheres to the polycentric strategy is open to learning and eager to make adjustments to suit local needs while also allowing locals to fill executive roles in its subsidiaries abroad (Lakshman et al., 2017). This lays the framework for the firm to adapt to the local environment. A geocentric orientation, on the other hand, is a mix of ethnocentric and polycentric perspectives that 16 demonstrates how a firm’s global strategy can simultaneously meet the demands and requirements of the local community (Lakshman, 2015).